Precursors and Chemicals Frequently Used in the Illicit Manufacture of Narcotic Drugs and Psychotropic Substances 2020 - International Narcotics Control Board (United Nations, 2021)
This report summarizes the actions taken by Governments and by the International Narcotics Control Board (INCB) on precursors to prevent chemical diversion and to implement the provisions of the United Nations Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances of 1988. The Report contains an account of the activities carried out during the reporting period; provides an overview of the major trends and developments in licit trade and trafficking in and illicit use of individual chemicals; contains a summary of seizures, cases of suspicious and stopped shipments, and diversions or attempted diversions; and details activities associated with illicit drug manufacture.